Reviews of Uzbek history textbooks. The view from Russia - Abashin, Sergey (Georg-Eckert-Institut für Internationale Schulbuchforschung, 2010)
In 2002, D. Rurikov, the ambassador of the Russian Federation in Uzbekistan, sent a letter of protest to the Russian Federation Ministry of Publishing and Information against the publication in the Republic of Uzbekistan of a textbook (in the Russian language) for 9th grade general education school. In the opinion of the ambassador, the textbook authored by Zh. Rakhimov, in which the Turkestan territory within the Russian Empire was discussed (the second half of the 19th century and early 20th century) had an “anti-Russian tendency,” was “extremely biased,” and “negatively” covered the events of the 19th century, “obscuring” the real historical picture of that time. D. Rurikov surmises that the “History Book of Zh. Rakhimov,” is one of the reasons why, in recent years, 300,000 Russians left Uzbekistan and moved to new areas. In the ambassador’s opinion, what was preferable was a “more correct” textbook by G.A. Khidoyatov and V.A. Kostetsky, although it “provoked many questions.” The purpose of this evaluation is to elucidate the following questions: 1. Whose position does the textbook reflect? 2. Does the textbook express the facts accurately? 3. Is there an “anti-Russian tendency” in the indicated textbooks?
Kostenfreier Zugang. - Lizenz: creative commons: by-nc-nd
Keywords: Usbekistan; Russlandbild; Geschichtsunterricht; Schulbuch